2021
DOI: 10.1073/pnas.2106210118
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β peptide dimers undergo a random coil to β-sheet transition in the aqueous phase but not at the neuronal membrane

Abstract: Mounting evidence suggests that the neuronal cell membrane is the main site of oligomer-mediated neuronal toxicity of amyloid-β peptides in Alzheimer’s disease. To gain a detailed understanding of the mutual interference of amyloid-β oligomers and the neuronal membrane, we carried out microseconds of all-atom molecular dynamics (MD) simulations on the dimerization of amyloid-β (Aβ)42 in the aqueous phase and in the presence of a lipid bilayer mimicking the in vivo composition of neuronal membranes. The dimeriz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
103
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(120 citation statements)
references
References 69 publications
8
103
1
Order By: Relevance
“…Previously, it has been shown that electrostatic interactions between the highly charged N‐terminal domain and residues F20‐A30 with mixed membranes are the driving force for the association of the dimer to the surface of the lipid bilayers 37 . Herein, residues G25‐A30 in conformations A2, A4, and C1 to C3 interact with the DOPC bilayer.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Previously, it has been shown that electrostatic interactions between the highly charged N‐terminal domain and residues F20‐A30 with mixed membranes are the driving force for the association of the dimer to the surface of the lipid bilayers 37 . Herein, residues G25‐A30 in conformations A2, A4, and C1 to C3 interact with the DOPC bilayer.…”
Section: Resultsmentioning
confidence: 96%
“…Previously, computational studies examined the binding of Aβ dimers on membrane surfaces, 36 , 37 , 38 and as transmembrane aggregates 28 , 39 , 40 , 41 on surface of different types of membranes. Some of these studies investigated Aβ dimer fragments, such as Aβ 17–42 28 and Aβ 29–42 .…”
Section: Introductionmentioning
confidence: 99%
“…The importance of GM1 in the Aβ–membrane interaction has also been demonstrated for another membrane model. 42 …”
Section: Resultsmentioning
confidence: 99%
“… 40 , 41 A different neuronal membrane model was used to study the dimerization of Aβ42 near the membrane using MD simulations. 42 In this work, we also used all-atom MD simulations, as they were successful in characterizing Aβ monomers and low-weight oligomers in solution 43 45 and on the membrane surface. 31 , 32 We studied three systems, including pure membrane without Aβ, membrane–dodecamer complex, and membrane–fibril complex.…”
Section: Introductionmentioning
confidence: 99%
“…After incubation, the spectra of all variants changed drastically, featuring a minimum at ~216–227 nm and a maximum at ~196 nm ( Figure 3 B). This indicated a transition to β-sheet secondary structure [ 31 ].…”
Section: Resultsmentioning
confidence: 99%